A Study on Flat Slab Assessment with ETABS Software (International Journal of Innovative Research in Engineering & Management, 2021)
Flat slabs are becoming increasingly fashionable these days, both  architecturally and aesthetically. Flat slabs are gaining popularity  these days due to their numerous benefits. Flat slabs are utilised in  the construction of high-rise structures because they lower building  height, allow for easy reinforce placement, require less time to  build, and are easier to shape. Flat slab construction is commonly  utilized in reinforced concrete structures all over the world because  it decreases the cost of form work, construction time, and is simple  to install. Without the need of beams, the floor slab system directly  supports the columns. In general, the most common challenge  encountered when constructing a flat slab is punching shear and  flexure shear failure. In my research, I used ETABS software to  develop flat slabs for flexural shear.
Keywords: Flat Slabs; flexure shear; Drop; ETABS software